Enhancing Short Story Writing through Experiential Learning Integrated with Wordwall Budaya: Unveiling the Role of Learning Motivation - Azmi, Muhammad Fauzi; Winarni, Retno; Yulisetiani, Septi (Universitas Pendidikan Ganesha, 2025)
The low proficiency in short story writing among elementary school students, coupled with limited learning motivation in literacy-based instruction, remains a critical issue in educational practice. The absence of instructional models that effectively integrate cognitive and affective aspects contributes to this condition. This study aims to analyze the effectiveness of the Experiential Learning model integrated with Cultural Wordwall in enhancing students’ short story writing skills and fostering their learning motivation. A quantitative approach with a quasi-experimental method and a nonequivalent control group design was employed. The study involved 27 fifth-grade students selected through cluster random sampling. Data were collected using a short story writing test and a learning motivation questionnaire. The data were analyzed using descriptive statistics and independent t-tests to examine differences between the experimental and control groups. The findings indicate that the implementation of Experiential Learning integrated with Cultural Wordwall significantly improves students’ narrative writing abilities while simultaneously enhancing their learning motivation. These results suggest that the instructional model can serve as an effective alternative strategy for developing both cognitive and affective competencies in elementary literacy education.